Influence of commissioned provider type and deprivation score on uptake of the childhood flu immunization. (12th June 2019) - Christensen, Hannah; Reynolds, Rosy; Kwiatkowska, Rachel; Brooks-Pollock, Ellen; Dominey, Matthew; Finn, Adam; Gjini, Ardiana; Hickman, Matthew; Roderick, Marion; Yates, Julie
Abstract: Background: Since 2015/16 the UK seasonal influenza immunization programme has included children aged 5 and 6 years. In the South West of England school-based providers, GPs or community pharmacies were commissioned to deliver the vaccine depending on the locality. We aimed to assess variation in vaccine uptake in relation to the type of commissioned provider, and levels of socioeconomic deprivation. Methods: Data from the South West of England (2015–16 season) were analysed using multilevel logistic regression to assess variation in vaccine uptake by type of commissioned provider, allowing for clustering of children within delivery sites. Results: Overall uptake in 5 and 6 year olds was 34.3% (37 555/109 404). Vaccine uptake was highest when commissioned through school-based programmes 50.2% (9983/19 867) and lowest when commissioned through pharmacies, 23.1% (4269/18 479). Delivery through schools resulted in less variation by site and equal uptake across age groups, in contrast to GP and pharmacy delivery for which uptake was lower among 6 year olds. Vaccine uptake decreased with increasing levels of deprivation across all types of commissioned provider. Conclusion: School-based programmes achieve the highest and most consistent rates of childhood influenza vaccination. Interventions are still needed to promote more equitable uptake of the childhood influenza vaccine.